Tingkat Hygiene dan Kandungan Escherichia coli pada Air Tebu yang Dijual Sekitar Kota Medan - Simanjuntak, Benny M.P; Hasan, Wirsal; Naria, Evi (Politeknik Kesehatan Tanjungkarang, 2018)
WHO (World Health Organization) mentions that water quality is biologically determined by the presence of E. coli bacteria. The content of E.Coli bacteria allowed in drinking water is 0 per 100 ml of sample. Sugar cane juice is one of the most E.Coli contaminated beverages. E. coli can cause disease associated with digestion such as diarrhea and including urinary tract infections, gastroenteritis, meningitis, peritonitis, and wound infections. The purpose of this study was to analyze the relationship of sanitary hygiene of vendors and environment with Escherichia coli content in sugar cane juice. The research was an analytic research using cross-sectional design approach. The sample of this study was 30 sugar cane vendors around Medan city. Data analysis using Pearson and linear regression test. Measurement aspects were sugar cane processing, transportation, sugar cane storage, sugarcane transportation and serving of sugar cane juice. The results showed a significant relationship between processing (p=0,00), location (p=0,02), transportation (p=0,00) and serving (p=0,00) with the present of E.Coli on sugarcane. It is suggested to the government conducting supervision and educates the sugarcane vendors to prepare their products based on regulation of the District Health Office.